Comparison of Joinery Methods on the Strength of Joining Aluminum Alloy and Steel Parts in a Vehicle. Issue 1 (1st December 2022) - Ding, Yichen; Cai, Mingxin; Yu, Xiaoxuan
Abstract: The modern society greatly utilizes automobiles to fulfill the requirements of transport, and it is logically necessary to research the most efficient joinery method arrangements to construct automobiles. In the contemporary stage of joinery technology, the three mainstream methods are bolting, riveting and welding, and among these joinery methods, bolting could be used for cylinder head and cylinder block, riveting might be the most suitable means for aluminum alloy and steel in vehicle., and welding would be most appropriate for doors, bottom plates and body assemblies. These different methods have various advantages and disadvantages in their applications, as their theories and principles are all but the same. This paper also discussed the methods of joinery that should be used in parts of the automobile body and the future expectation of more novel connection methods that would appear to replace traditional ones.